Pengaruh Literasi Teknologi Pertanian Berbasis Augmented Reality terhadap Minat dan Kesadaran Generasi Z pada Modern Farming di Kota Parepare - Irninthya Nanda Pratami Irwan; Ashadi Amir; Wahyuddin Wahyuddin (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Regeneration in the agricultural sector is not going well because Generation Z is more interested in working in technology and creative industries, resulting in an aging workforce among farmers. The aim of this research is to create agricultural literacy media using Augmented Reality technology as an effort to enhance the interest and understanding of Generation Z towards the agricultural sector. The initial stage of the research involves creating a technology literacy media for agriculture using an Augmented Reality-based application. The second stage is carried out by providing literacy to Generation Z engaged in the agricultural sector in the form of introducing agricultural technology through the use of Augmented Reality-based literacy media. Data analysis from the research was conducted to measure the level of understanding and the increase in interest and awareness of Generation Z towards the modern agricultural sector after technology literacy was implemented. The results of the multiple linear regression test indicate that interest in modern farming is influenced by agricultural knowledge, interest in agriculture, and awareness of modern farming, with a value of 71.2%.